Odynophagia after Cardiac Catheterization: A Rare Complication in the Presence of Aberrant Subclavian Artery. (2nd December 2020) - Naidu, Moumita; Singh, Robby; Zughaib, Marcel
Abstract : Background . Vascular complications from transradial cardiac catheterization are uncommon. Mediastinal hematoma is a rare complication with life-threatening potential. We present a case of a patient who underwent cardiac catheterization and subsequently experienced odynophagia from injury to an aberrant subclavian artery that led to a mediastinal hematoma. Case Report . A 59-year-old female with past medical history of coronary artery disease presented with complaints of angina and underwent a transradial cardiac catheterization. Immediately after the procedure, the patient complained of chest pain and odynophagia. EKG and echocardiogram were unremarkable, and a CT scan of the chest demonstrated an ill-defined fluid collection present in the superior mediastinum and an aberrant right subclavian artery. The patient was closely monitored in the Intensive Care Unit, and the patient remained hemodynamically stable throughout the admission. The patient was subsequently discharged home in good condition and did well on outpatient follow-up. Conclusion . Vascular injuries associated with delivery of standard radial catheters in the subclavian artery are rare, with very few cases reported in the literature. We presented the case of a patient who had a previously unidentified right aberrant subclavian artery with a retroesophageal course which precipitated the hematoma and subsequently resulted in odynophagia despite an uncomplicated catheterization. This rare complication of a commonplace procedure necessitates prompt recognition, appropriate hemodynamic management, and possible repair of the injured vessel to appropriately manage a potentially life-threatening condition.